Із народу не викенеш: діалектний словник фразеологізмів - Мацюк, Зоряна Сергіївна; Matsiuk, Zoriana S. (Східноєвропейський національний університет імені Лесі Українки, 2006)
Окреслено матеріал до Фразеологічного словника Західного Полісся. Проаналізовано фраземи, які не увійшли до «Фразеологічного словника української мови». Схарактеризовано основні принципи структури словникових статей. The paper deals with the phraseological vocabulary of Western Polessia region. A phrazelological unit that are absent in the “Ukrainian phraseological vocabulary” were analyzed in the paper under consideration. The main structure principles of the lexicographic papers were defined. The main principles of lexicographic articles structure are characterized.
Vocabulary of ethnic comparisons in Western Polessia dialects
Keywords: vocabulary; phrazelological unit; dictionary entry; Western Polessia; словник; фразема; словникова стаття; Західне Полісся